Poverty, social sector development and the role of the World Bank - Hicks, Norman (Estudios de Economía, 2016)
This paper summarizes recent trends in poverty in Latin America, and the relationship between poverty and social sector development. It notes that World Bank Lending for social sector development in at the region has increased substantially in the past five years, and will continue to expand. Social sector lending projects of the Bank attempt to both increase the quality of human resource development, and focus the delivery of services to the poor, in order to both eliminate the worst manifestations of poverty, and to increase the human capital and earnings capacities of the poor.